FAMILY FACTORS INFLUENCING THE DEVELOPMENT OF JUVENILE DELINQUENCY AMONG PUPILS IN KABETE REHABILITATION SCHOOL IN NAIROBI COUNTY, KENYA - Mwanza, Martin Mwaka (Advances in Social Sciences Research Journal, 2020)
This paper uses data collected for an MA Thesis on the family factors influencing the development of juvenile delinquency among pupils in Kabete Rehabilitation School in Nairobi County, Kenya. This study has been necessitated by continued concern among policymakers, practitioners, citizens, and researchers about the rising cases of juvenile delinquency in Nairobi County. Although there had been speculations that family factors sit at the core of the trigger factors, there has never been a detailed and systematic inquiry and analysis of this problem. The study was guided by several specific objectives; the first objective examined the range of family factors that influenced the development of juvenile delinquency among pupils in Kabete Rehabilitation School in Nairobi County, Kenya while the second objective examined how family types influenced the development of juvenile delinquency among pupils in Kabete Rehabilitation School in Nairobi County, Kenya. Last but not least, the study assessed the multiplier effects of juvenile delinquency among pupils in Kabete Rehabilitation School in Nairobi County, Kenya. The study adopted a qualitative case study research design and purposive sampling technique. A sample size of 60 respondents who comprised of 30 parents, 24 pupils, 4 teachers and 2 administrators was adopted. The collected data was analyzed thematically and presented in verbatim quotes. The study revealed a relationship between family factors, family types and development of delinquency among juveniles. Family attachment and family conflict are risk factors for delinquency. Further, this study established that not all children follow the same road to delinquency; different life-experience combinations will produce different delinquent activity. For instance, positive parenting behaviours in the early years and later in adolescence tend to serve as barriers mitigating juvenile activity and encouraging teenagers who are already involved in criminal conduct to refrain from more crime. In matters policy, this study recommends interventions with the help of other social institutions such as religion and others that have a direct bearing on children growth and development like the government children departments to deeply engage in altering parenting practices aiming to promote better socialization of the child and also reduce engagement in negative outcomes such as delinquency. The government may consider starting up free family counseling clinics and rehabilitation centers to address or counter any social and behavioural defects that result from inadequate parenting such as delinquency.